Innovative Methods in the Educational Processes of Contemporary Higher School - Evgeny Vasilyevich Shirshov; Tatyana Sergeevna Butorina; Valentina Nickolaevna Novikova; Churbanov Alexander Leonidovich (International Review of Management and Marketing, 2016)
Based on the analysis of current trends in the development of higher education, upgrading the structure of curricula and teaching methods, experience of using information and communication technologies, some innovative methods of didactic software are discussed in the article. The systematic approach in the educational process of higher education, the justification of the composition, structure and patterns of major components of the educational activities, the creation of the necessary organizational and pedagogical conditions for the application of multicomponent technology implementation approach based on multivariate data analysis methods, and electronic information and educational technologies are of great importance in the study. In conclusion the article emphasizes that the main problem of this study was concentrated on applying mathematical and statistical tools in the field of humanities. In the context of a deeper understanding of the scientific and technological achievements justified and presented theoretical background for further development of future specialists training.